Salmonella prevalence and microbiological contamination of pig carcasses and slaughterhouse environment - Francesca Piras; Federica Fois; Roberta Mazza; Miriam Putzolu; Maria Luisa Delogu; Pier Giorgio Lochi; Sergio Pino Pani; Rina Mazzette (Italian Journal of Food Safety, 2014)
In seven EC swine abattoirs Salmonella prevalence (ISO 6579/2002) and serotypes of 25 piglets, 61 finishing pigs (lymph nodes, colon content, carcass and liver surface) and slaughterhouse environments (scalding water, surfaces in contact with meat and not in contact with meat) were investigated. Moreover, aerobic colony count [total viable count (TVC); ISO 4833] and Enterobacteriaceae (ISO 21528-2) of piglets and finishing pigs’ carcasses were evaluated, and the results compared with EU process hygiene criteria (Reg. EC 2073/2005). Salmonella was not isolated in any of the piglets samples. Prevalence differed between slaughterhouses (P<0.5), and Salmonella was isolated from 39 of 244 samples of finishing slaughtered pigs (15.9%) and from 4 of 45 environmental samples (8.9%). In pig samples, carcasses showed the highest prevalence (18%) followed by colon content (14.8%), lymph nodes (13%) and liver (1.6%). S. Anatum was the most prevalent serotype (71.8%), followed by S. Derby (33.3%), S. Bredeney (5%) and S. Holcomb (2.5%). Between environmental samples, S. Anatum (50%), S. Bredeney and S. Derby (25%) were identified. Total viable mean counts (log10 CFU/cm2) of carcass surfaces ranged from 4.6 and 5.7 for piglets, and from 4.6 and 5.9 for finishing pigs, while Enterobacteriaceae ranged between 1.1 and 5 for piglets and between 2.1 and 5.3 for finishing pigs. These results were not in compliance with EU performance criteria. Total aerobic viable counts and Enterobacteriaceae mean levels of environmental samples appeared critical, particularly referred to surfaces in contact with meat (splitting equipment) and indicated an inadequate application of good manufacturing and hygiene practices during slaughtering and sanitisation.